A pilot study comparing two physiotherapy techniques in patietnts with cystic fibrosis - S. M. Milne; C. J. Eales (AOSIS, 2004)
The flutter is a simple hand held device designed to facilitate the mobilisation of excess bronchial secretions by means of oscillating positive pressure. Traditionally patients at the Johannesburg Hospital Cystic Fibrosis clinic used the active cycle of breathing technique as a means of facilitating secretion mobilisation and clearance. When the flutter became available in South Africa in 1999 many cystic fibrosis patients wanted to change to this technique. Minimal research has been conducted comparing these two techniques. The aim of this pilot study was therefore to determine which technique is more effective in the mobilisation of  secretions in cystic fibrosis patients. The pilot study was conducted on seven cystic fibrosis patients (mean age 28 years, range 16-42 years) admitted to the Johannesburg Hospital for antibiotic therapy. The study lasted four days and consisted of two treatment days  separated by a washout day on which no physiotherapy was performed. Patients randomised into Group A performed the flutter technique on day two and the active cycle of breathing technique on day four. Group B performed the active cycle of breathing technique on day two and the flutter on day four. The techniques were performed twice a day for  15 minutes. The measurements taken were daily 24-hour sputum samples and daily lung function tests. A questionnaire to determine patient preference to a technique concluded the study.  The results showed no statistical difference between the two techniques with regard to sputum weight or lung function (p<0.05). The questionnaire indicated that on a whole, patients had no preference for a technique.